2021
DOI: 10.1002/chem.202103286
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Organic Crystals Based on Barbituric Derivative: Multi‐faceted Bending and Flexible Optical Waveguide

Abstract: Elastic organic single crystals with light-emitting and multi-faceted bending properties are extremely rare. They have potential application in optical materials and have attracted the extensive attention of researchers. In this paper, we reported a structurally simple barbituric derivative DBDT, which was easily crystallized and gained long needle-like crystals (centimeter-scale) in DCM/CH 3 OH (v/v = 2/8). Upon applying or removing the mechanical force, both the ( 100) and ( 040) faces of the needle-like cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 71 publications
(96 reference statements)
0
23
0
Order By: Relevance
“…35 Additionally, the dispersion dominated interactions such as C−H•••O, C−H•••S, and C−H••• π along with π-stacks act as a "structural buffer", allowing dissipation of strain energy without irreversible deformation. 12,17,36 The interactions in the orthogonal direction, i.e., N−H S4). The orthogonal arrangement of these interactions with respect to the collective dispersive interactions in the crystalline arrangement accounts for the preliminary conditions for existence of elasticity in organic crystalline materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Additionally, the dispersion dominated interactions such as C−H•••O, C−H•••S, and C−H••• π along with π-stacks act as a "structural buffer", allowing dissipation of strain energy without irreversible deformation. 12,17,36 The interactions in the orthogonal direction, i.e., N−H S4). The orthogonal arrangement of these interactions with respect to the collective dispersive interactions in the crystalline arrangement accounts for the preliminary conditions for existence of elasticity in organic crystalline materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The computed interaction energy (energy frameworks, Crystal Explorer 17.5, details in section S5 in the SI) reveals the significance of dispersion dominated molecular stacks involving π–π interactions ( E tot = −37.8 kJ/mol, E disp = −67.15 kJ/mol; E disp value is obtained after multiplying the dispersion contribution mentioned in Table S4 with the k disp scale factor) . Additionally, the dispersion dominated interactions such as C–H···O, C–H···S, and C–H··· π along with π-stacks act as a “structural buffer”, allowing dissipation of strain energy without irreversible deformation. ,, The interactions in the orthogonal direction, i.e., N–H···O and C–H···O hydrogen bonds formed between TU and DMSO, are primarily electrostatically driven interactions ( E tot = −79.7 and −29.6 kJ/mol; E elec = −93.016 and −30.01 kJ/mol obtained after multiplying the electrostatic contribution with the k elec scale factor; Table S4). The orthogonal arrangement of these interactions with respect to the collective dispersive interactions in the crystalline arrangement accounts for the preliminary conditions for existence of elasticity in organic crystalline materials.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers have excellent advantages, including light weight, good processability, and diverse stimuli methods, and have been widely used in actuator research . Organic crystals have the characteristics of easy modification and characterization of molecular structure and excellent luminescence properties, showing tremendous potential for applications in optical waveguides, photonic technology, , lasers, OLEDs, and so forth. However, the hard and brittle properties of crystalline materials often limit their application .…”
Section: Introductionmentioning
confidence: 99%
“…[15] Jia et al synthesized a barbituric derivative and the crystal of that compound showed reversible and multi-faceted bending behavior. [16] The pursuit of high elastic performance of fluorescent organic single crystals remains a work in progress. When high performance elastic crystals are achieved, organic single crystals will have more significant application potential in photonic devices and circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al. synthesized a barbituric derivative and the crystal of that compound showed reversible and multi‐faceted bending behavior [16] . The pursuit of high elastic performance of fluorescent organic single crystals remains a work in progress.…”
Section: Introductionmentioning
confidence: 99%